Biorational management of okra jassid (Amrasca devastans) - Akramuzzaman, M; Uddin, MM; Islam, KS (Progressive Agriculture, 2018)
An experiment was carried out to appraise the comparative efficacy of some biorationals against okra jassid at the Field Laboratory, Department of Entomology, Bangladesh Agricultural University, Mymensingh during January to June 2016. The experiment was accomplished using three botanical oils (Neem oil@ 2ml/L, Mahogany oil @2ml/L & Karanja oil @2ml/L) and four microbial insecticides (Spinosad @ 1ml/ L, Beauveria bassiana @ 1 g/ L, Buprofezin @ 2ml/L, Emamectin benzoate @ 1g/L) along with control. Among various biorationals the mean number of nymph plant-1 varied significantly (p<0.01, p<0.05) after 1st, 2nd and 3rd spray. After 1st and 2nd spray, Beauveria showed the best results both at 3 DAT (0.00 & 2.33, respectively) while after 3rd spray Mahogany (0.00) performed best at 3 DAT compared to other treatments including control (4.00). In number of adult plant-1 effectiveness was reflected on Neem (0.66) among various biorationals at 3 DAT after 2nd spray. Similarly, at 5 and 7 DAT, the lowest number of adult was observed at Emamectin (1.66, 1.00), respectively. It revealed that Neem and Emamectin had strong efficacy in controlling okra jassid in comparison to their control (7.33, 11.33), respectively. After 3rd spray, the efficacy of different bioratioanls in managing okra jassid was significant (p<0.01). The Buprofezin showed the best performance both at 3 and 5 DAT (0.66 & 1.66, respectively). Similarly, the number of curled leaf plant-1 varied significantly (p<0.05, p<0.01) after both 1st 2nd and 3rd spray than the control. The lowest number of curled leaf plant-1 was observed in Neem (0.66) treated plants at 3 DAT after 2nd spray. This data revealed that the Neem had strong effect on okra jassid management. The number of curled leaf plot-1 also varied significantly (p<0.01) after 2nd and 3rd spray than the control. The highest infestation was always found in control treatment. The results indicated that Beauveria bassiana had strong efficacy in controlling okra jassid followed by Neem oil, Buprofezin and Emamectin benzoate in comparison to control. Therefore, it might be concluded that these biorational insecticides could be used as eco-friendly management strategy for okra jassid and can be incorporated in developing IPM programme for jassid. Progressive Agriculture 29 (3): 205-212, 2018